1991
DOI: 10.1108/03090569110139166
|View full text |Cite
|
Sign up to set email alerts
|

Marketing‐orientation Revisited: The Crucial Role of the Part‐time Marketer

Abstract: Most of a company′s marketing is not carried out by the professional full‐time marketer but by the amateur part‐time marketer (PTM), who is omnipotent both inside and outside a company. The PTM influences customer relations and revenue without belonging to the marketing or sales department. Unless the PTM is recognised, marketing can never be efficient. Although this is in essence a matter of marketing‐orientation, which of course is not new, it has been found to be a much more profound and difficult issue to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
278
0
17

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 427 publications
(301 citation statements)
references
References 0 publications
6
278
0
17
Order By: Relevance
“…"Marketers, whether of full-time stature or in 'the crucial role' (Gummesson, 1991) of part-time marketer, whether working in a large or micro enterprise, whether operating in a big or small network, need to deepen existing expertise and learn new competences," (O'Driscoll et al, 2000: 193). During the creation phase, the INV will face changes and unforeseen circumstances that will require slight variations to the initial project (Greiner, 1972).…”
Section: Influence Of Marketing Capabilities On International Performmentioning
confidence: 99%
“…"Marketers, whether of full-time stature or in 'the crucial role' (Gummesson, 1991) of part-time marketer, whether working in a large or micro enterprise, whether operating in a big or small network, need to deepen existing expertise and learn new competences," (O'Driscoll et al, 2000: 193). During the creation phase, the INV will face changes and unforeseen circumstances that will require slight variations to the initial project (Greiner, 1972).…”
Section: Influence Of Marketing Capabilities On International Performmentioning
confidence: 99%
“…A common view among researchers supports the role of internal marketing as encouraging employees to adopt and display market orientated behavior (Gronroos, 1981;Gummesson, 1991). Gronroos (1990) suggests that internal marketing can change employee's attitude and behaviors, and establish the corporate culture.…”
Section: Internal Marketingmentioning
confidence: 99%
“…Since most nonprofit organizations are dependent on WOM to generate funding, donations and all kinds of support member co-creation behaviours such as acting as part-time marketers (cf. Gummesson, 1991) are worth considering. Multivariate analysis further showed that spreading WOM about the supported organization was significantly related to altruistic motives (higher for part-time marketers), selfinterest motives (higher for part-time marketers) and age (higher for older members, i.e.…”
Section: How Do Members Interact?mentioning
confidence: 99%